Exercise intensity and shooting position modulate fixation behavior and 2-point shooting accuracy in elite female basketball players: An eye-tracking study - Xiaokun Zhang; Sunnan Li; Chunzhou Zhao (PLoS ONE, 2026)
Visual attention plays a crucial role in basketball shooting, yet how it adapts under varying exercise intensities and from different shooting positions remains poorly understood, especially in elite female athletes. This study examined the effects of exercise intensity (low, moderate, high) and shooting position (left 45°, 90°, right 45°) on fixation behavior and 2‑point shooting accuracy in elite female basketball players. Twenty‑two players from a championship‑winning university team performed two‑point shots from three positions under three intensity conditions, each defined by heart‑rate zones (%HRmax). Fixation metrics (number of fixations, fixation duration, distribution) were recorded using Tobii Glasses 3. Data were analyzed using two‑way repeated‑measures ANOVA and generalized linear mixed‑effects models (GLMMs) with a binomial distribution for trial‑level accuracy; Pearson correlations are reported descriptively. Exercise intensity significantly influenced all fixation metrics. High intensity led to increased fixations across all areas of interest (hoop, backboard, net) and longer total fixation duration, indicating higher cognitive load. Moderate intensity was associated with the lowest total number of fixations and shortest duration, reflecting efficient visual processing. Shooting position also affected fixation: the 90° position attracted the most fixations and longest duration on the hoop ( F = 4.56, p = 0.017, η p 2 = 0.19, 95% CI [0.02, 0.37]), while the 45° positions shifted attention toward the backboard. Fixation duration on the hoop positively correlated with accuracy under high intensity ( r = 0.499, p = 0.021, 95% CI [0.10, 0.76]), whereas number of fixations negatively correlated with accuracy across intensities. Moderate intensity promotes optimal visual‑attentional control and shooting accuracy in elite female athletes, whereas high intensity disrupts fixation stability and increases cognitive load. Position‑specific adaptations in visual strategy were also observed. These findings support the use of intensity‑ and position‑based visual training to enhance shooting performance under realistic game conditions.